1997
DOI: 10.1021/jo970343o
|View full text |Cite
|
Sign up to set email alerts
|

Studies toward the Synthesis of Vinigrol. First Construction of the Tricyclic Ring System

Abstract: The first synthesis of a functionalized tricyclic skeleton of vinigrol is described. The key step involved an anionic oxy-Cope rearrangement of bicyclic allylic alcohol 18, readily prepared by highly stereoselective addition of vinyl magnesium chloride to the hydroxy enone 15b. Introduction of the tertiary hydroxy group at carbon 8a was achieved by an unexpected hydration of 30 with aqueous trifluoroacetic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The bicyclic scaffolds of 7 − 9 were envisioned to arise from two Diels−Alder reactions between dienes 12 and 23 , respectively, and a reactive electron-deficient ethene equivalent. Commercially available phenyl vinyl sulfone was the dienophile of choice since the electron-withdrawing sulfonyl group could be smoothly eliminated from the cycloaddition products . While the cycloaddition of diene 12 was expected to proceed uneventfully, the diastereoselectivity of the Diels−Alder reaction of diene 23 was rather unpredictable, though the bulky lateral substituent could, in principle, influence reagent approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bicyclic scaffolds of 7 − 9 were envisioned to arise from two Diels−Alder reactions between dienes 12 and 23 , respectively, and a reactive electron-deficient ethene equivalent. Commercially available phenyl vinyl sulfone was the dienophile of choice since the electron-withdrawing sulfonyl group could be smoothly eliminated from the cycloaddition products . While the cycloaddition of diene 12 was expected to proceed uneventfully, the diastereoselectivity of the Diels−Alder reaction of diene 23 was rather unpredictable, though the bulky lateral substituent could, in principle, influence reagent approach.…”
Section: Resultsmentioning
confidence: 99%
“…It must be stressed that the success of the alkylation of sulfone 24 strongly depended on the use of DMPU as cosolvent, since in THF alone the reaction afforded significantly lower yields. With diene 23 in hands, our attention was directed to the study of the crucial Diels−Alder reaction with phenyl vinyl sulfone (Scheme ) . In the event, the cycloaddition of 23 proceeded satisfactorily at a temperature significantly higher than that for the analogous Diels−Alder reaction of diene 12 , i.e., at 155 vs 100 °C.…”
Section: Resultsmentioning
confidence: 99%
“…6 They demonstrated that alcohol 14 could be hydrated in such a way to afford triol 15 in modest yield. This was a significant achievement as it completed the critical cis -decalin ring fusion of vinigrol.…”
Section: Introductionmentioning
confidence: 99%